Les cartes des chemins de fer au Etats-Unis dans la deuxième moitié du 19ème siècle : quelques réflexions sur la représentation géographique et la géographie imaginaire - Mila DI NAPOLI-MARCHETTI (E-REA)
In the second half of the 19th century, the United States transcontinental railroads stimulated an unprecedented cartographic activity. The representation of a geographical reality, hidden behind the mapping process, may lead to the disclosure of another and unexpected geography. Since any map is regarded as a tool of communication, the railroad maps, published in the United States since 1853, may be considered a privileged tool intended to convey a message of information, propaganda and advertising glorifying the economic and political success, hiding behind graphic representations featured in various forms.